Overview of long-period ground motion professional works in Japan - Shuai Wang; Zhinan Xie (地震科学进展)
Long-period ground motion (LPGM) can result in prolonged vibration and even damage or collapse of structures and infrastructure with long natural vibration periods. With the emergence of flexible structures such as high-rise buildings and large oil tanks in our country, there is an urgent need to effectively mitigate LPGM-related damage. However, the national intensity rapid reporting and early warning project currently does not include early warning or related information dissemination for LPGM. This paper introduces in detail the development of Japan’s LPGM business system, including the initial proposal, system construction, and its continuous improvement. It describes key technologies involved in the development of this system, such as the classification of LPGM and the establishment of LPGM prediction technology. The paper also summarizes the application of the LPGM business system and the research and development of supporting disaster reduction facilities. Finally, based on Japan’s experience in constructing a long-period ground motion service system “Observe business first, then develop predictive technologies, and finally implement predictive services”, some suggestions are proposed for the future construction of China’s long-period ground motion service system.